Designing and Fabrication of Nano-Hydroxyapatite and Curcumin-Loaded Chitosan/PVA Nanofibrous Mats for Potential Use as Wound Dressing Biomaterials - Amira M. EL-Rafei; Giorgia Maurizii; Annalisa Aluigi; Giovanna Sotgiu; Marianna Barbalinardo; Tamara Posati (Nanomaterials)
Chitosan/polyvinyl alcohol nanofibrous mats loaded with nano-hydroxyapatite and/or curcumin are successfully fabricated by the electrospinning method for the first time. Nano-hydroxyapatite is prepared by the co-precipitation method. The XRD pattern of calcined powder at 700 °C for 2 h reveals the presence of hydroxyapatite as a sole phase. FT-IR confirms its purity. The morphology of the hydroxyapatite is studied by HR-TEM. Nano-hydroxyapatite and curcumin are added at 5 wt% with respect to the polymer weight. XRD, FE-SEM, FT-IR, and HR-TEM are used to characterize the fabricated nanofibrous mats. The results confirm the successful loading of nano-hydroxyapatite and curcumin within the fabricated mats. The in vitro antimicrobial results show that most of mats have significant antimicrobial effects against E. coli and S. aureus. The fabricated matd are biocompatible with fibroblasts and the presence of curcumin increases cell viability. Curcumin release from both CS/PVA/Cur and CS/PVA/HA/Cur nanofiber mats principally follows the Korsmeyer–Peppas and Peppas–Salhin models.